Bilateral Strength Asymmetry in Elite Youth Soccer Players: Differences between Age Categories - Maros Kalata (MDPI AG, 2021)
The strength asymmetry of athletes as a negative health and performance factor is increasingly being researched in sports with a high load on the dominant limb when some specific unilateral movements, such as passing, jumping, and tackling, are required. This study aimed to determine the level of isokinetic strength bilateral asymmetry (BA) among knee extensors (KEs) and knee flexors (KFs) of elite youth soccer players. The sample (n = 87) consisted of three age categories of under 13 (U13), under 15 (U15), and under 17 (U17) years old. Isokinetic dynamometry was used to obtain the maximum peak torque of the KEs and KFs in the dominant and non-dominant lower limbs during concentric muscle contraction. The analysis revealed significantly lower values (p < 0.05) of BA in KEs in U17 than in younger categories, U13 and U15, and higher values (p < 0.05) of BA in KFs in the U15 category than in the U17category. The majority of the players in the U15 category (68%) reached KFs BA higher than 10% in comparison with U13 players (50%) and U17 players (28% of players) (p < 0.05). Our results showed a significant effect of age category on BA levels in young soccer players. High incidences of increased BA in the lower limbs occurred in the younger categories (U13, U15) and subsequently decreased in the later adolescent stages.